PENGEMBANGAN POTENSI WISATA BAHARI DI DUSUN MEANG DESA BUWUN MAS KECAMATAN SEKOTONG KABUPATEN LOMBOK BARAT - Nuriadi Nuriadi; ander sriwi; I Gusti Ngurah Oka Widjaya; Lalu Mahsar (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2023)
Development of marine tourism potential in Meang Hamlet, Buwun Mas Village, Sekotong District, West Lombok Regency. However, in developing the potential as a tourist attraction, there are always inhibiting factors ranging from accessibility and supporting facilities. This study aims to analyze the potential of marine tourism in Meang Hamlet. So that it can then be used as a reference material for the local community and local government as well as the central level to develop marine tourism in Meang Hamlet. The research method used is the SECI model using the 4A development theory initiated by Sugiama including Attraction, Amenities, Ancilliary, and Accessibility. The methods used in collecting data are interviews, direct observation and documentation. The results of this study indicate that the development of marine tourism in Meang Hamlet, Buwun Mas Village, located in Sekotong District, is still not optimal when viewed from accessibility and amenity. Even though each region has a lot of potential that needs to be developed to become a tourist destination that attracts tourists to visit. This potential can be different and has its own unique value, this uniqueness then becomes a differentiator for other destinations, so Meang Hamlet has a myriad of potentials that can be processed into unique tourist destinations and can attract tourists to visit the area. The potential starts from an underwater park decorated with natural coral reefs and rare fish, white pepper sand, and long waves and is suitable as a location for diving, snorkeling, and surfing.